1984
DOI: 10.1161/01.cir.70.1.102
|View full text |Cite
|
Sign up to set email alerts
|

Importance of temporal heterogeneity in assessing the contraction abnormalities associated with acute myocardial ischemia.

Abstract: A number of recent two-dimensional echocardiographic studies have attempted to relate quantitative changes in short-axis left ventricular radial wall motion to underlying myocardial ischemia/infarction. The significance of temporal variation in the contraction sequence within these ischemic regions in the overall evaluation of segmental left ventricular dysfunction, however, remains undefined. To assess this, we examined the motion of 192 individual radii that intersected known ischemic segments at 16.7 msec i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…Consequently, although tardokinesia and mild forms of hypokinesia can be detected with this technique, they can be missed when only end-diastolic and end-systolic frames are used. 20,21 Furthermore, we compared WT in every bed to that of the normally perfused bed at each dose of dobutamine. Thus, a unique threshold for abnormality was used separately for each dog at each dobutamine dose, which allowed detection of subtle WT abnormalities that were not readily observed visually.…”
Section: Critique Of Our Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, although tardokinesia and mild forms of hypokinesia can be detected with this technique, they can be missed when only end-diastolic and end-systolic frames are used. 20,21 Furthermore, we compared WT in every bed to that of the normally perfused bed at each dose of dobutamine. Thus, a unique threshold for abnormality was used separately for each dog at each dobutamine dose, which allowed detection of subtle WT abnormalities that were not readily observed visually.…”
Section: Critique Of Our Methodsmentioning
confidence: 99%
“…Using the resting transstenotic pressure gradient (mm Hg), the stenosis stages were divided into mild, 10 -14 moderate, [15][16][17][18][19][20] and severe (Ͼ20 mm). For each stenosis level, a standard dobutamine stress protocol was performed with a baseline and up to four incremental 3-minute dobutamine stages (10 to 40 g/kg Ϫ1 · min Ϫ1 infused intravenously).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…First, the studies done to date have all required precise retrospective matching and aligning of the two-dimensional echocardiographic section with the pathologic section, a process that relies on internal landmarks that are distorted by the postmortem processing. 19 Second, Armstrong et al,20 in a preliminary report, found that at least some portion of this overestimation of ischemic region size was caused by inherent limitations of the two-dimensional echocardiographic analysis procedures used to evaluate regional left ventricular function. These procedures analyze thickening on a radial coordinate plot emanating from a floating center of mass and express extent of dysfunction as a percentage of the diastolic left ventricular circumference.…”
mentioning
confidence: 99%
“…We chose a strict criterion because many studies in both animals and humans have found that there is heterogeneity of contraction in normal myocardium." [25][26][27][28] Another factor affecting the risk region-infarct size relationship is the duration of coronary occlusion before reperfusion. In our study the infarct size was almost twice as large in the animals subjected to 2 hr coronary occlusions compared with that in animals subjected to 1 hr occlusions.…”
Section: Methodsmentioning
confidence: 99%